2021
DOI: 10.21203/rs.3.rs-385507/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Mirna Signature and Key Genes in Colorectal Cancer Lymph Node Metastasis

Abstract: Background: miRNAs and mRNAs can serve as biomarkers for the diagnosis, prognosis and therapy of colorectal cancer (CRC), whose metastasis to lymph node is closely related to the poor prognosis. The current study aimed to identify the novel gene signatures in the lymph node metastasis of CRC.Methods: GSE56350, GSE70574 and GSE95109 were downloaded from the Gene Expression Omnibus (GEO) database and 569 colorectal cancer statistics were also downloaded from the The Cancer Genome Atlas (TCGA) database. Different… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…In another recent study, clusters miR-17/92a-1, miR-106a/363, miR-106b/93/25 and miR-183/96/182 showed the strongest association with metastasis occurrence and poor patient survival (41). Similarly, Wang et al (42) observed that the miR-99a-HS3ST2-miR-100 axis, a novel miRNA-mRNA network, was associated with the presence of lymph node metastasis in CRC. Insights into the roles of miRNAs in cancer have established them as targets for novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 85%
“…In another recent study, clusters miR-17/92a-1, miR-106a/363, miR-106b/93/25 and miR-183/96/182 showed the strongest association with metastasis occurrence and poor patient survival (41). Similarly, Wang et al (42) observed that the miR-99a-HS3ST2-miR-100 axis, a novel miRNA-mRNA network, was associated with the presence of lymph node metastasis in CRC. Insights into the roles of miRNAs in cancer have established them as targets for novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 85%
“…It is a promising therapeutic research field to inhibit or replace microRNAs. [14] One study found that miRNA-424-5p regulated ferroptosis by targeting Acyl-CoA Synthetase Long Chain Family Member 4 in OC cells and indicated a potential therapeutic target for ovarian cancer. [15] Wu et al [16] found that the downregulated microRNA-1301-3p inhabited lung carcinoma cell proliferation and migration and has a strong negative correlation with Polymerase I and transcript release factor.…”
Section: Introductionmentioning
confidence: 99%